MENINGKATKAN KETERAMPILAN PROSES IPA DAN KARAKTER WASAKA MENGGUNAKAN MODEL PROBLEM BASED LEARNING, TEAM GAMES TOURNAMENT TERINTEGRASI STEM PADA SISWA KELAS VA SDN BASIRIH 1 BANJARMASIN - Nor Aida; Muhsinah Annisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the lack of process skills in science learning and the low value of the WASAKA character, including discipline and hard work, in the learning process. This is caused by learning methods that are still one way, lack of implementation of STEM, and lack of emphasis on character values. Solution efforts were made by combining the Problem Based Learning, Teams Games Tournament and STEM models. This research aims to analyze WASAKA's science process skills and character using Classroom Action Research (PTK). The research subjects were class VA students at SDN Basirih 1 Banjarmasin for the 2023/2024 academic year with 33 students. The data used is qualitative and quantitative. The research results showed an increase in science process skills from 0% to 97% and an increase in WASAKA character from 15% to 94% classically from cycles I to II. In conclusion, the combination of learning models is effective in improving science process skills and WASAKA character.